Annexin V+ Microvesicles in Children and Adolescents with Type 1 Diabetes: A Prospective Cohort Study - Vibeke Bratseth; Hanna D. Margeirsdottir; Gemma Chiva-Blanch; Martin Heier; Svein Solheim; Harald Arnesen; Knut Dahl-Jørgensen; Ingebjørg Seljeflot (Journal of Diabetes Research)
Background. Type 1 diabetes is a chronic disease including hyperglycemia and accelerated atherosclerosis, with high risk of micro- and macrovascular complications. Circulating microvesicles (cMVs) are procoagulant cell fragments shed during activation/apoptosis and discussed to be markers of vascular dysfunction and hypercoagulability. Limited knowledge exists on hypercoagulability in young diabetics. We aimed to investigate cMVs over a five-year period in children/adolescents with type 1 diabetes compared with controls and any associations with glycemic control and cardiovascular risk factors. We hypothesized increased shedding of cMVs in type 1 diabetes in response to vascular activation. Methods. The cohort included type 1 diabetics (n=40) and healthy controls (n=40), mean age 14 years (range 11) at inclusion, randomly selected from the Norwegian Atherosclerosis and Childhood Diabetes (ACD) study. Citrated plasma was prepared and stored at -80°C until cMV analysis by flow cytometry. Results. Comparable levels of Annexin V (AV+) cMVs were observed at inclusion. At five-year follow-up, total AV+ cMVs were significantly lower in subjects with type 1 diabetes compared with controls; however, no significant differences were observed after adjusting for covariates. In the type 1 diabetes group, the total AV+, tissue factor-expressing AV+/CD142+, neutrophil-derived AV+/CD15+ and AV+/CD45+/CD15+, and endothelial-derived AV+/CD309+ and CD309+/CD34+ cMVs were inversely correlated with HbA1c (r=‐0.437, r=‐0.515, r=‐0.575, r=‐0.529, r=‐0.416, and r=‐0.445, respectively; all p≤0.01), however, only at inclusion. No significant correlations with cardiovascular risk factors were observed. Conclusions. Children/adolescents with type 1 diabetes show similar levels of AV+ cMVs as healthy controls and limited associations with glucose control. This indicates that our young diabetics on intensive insulin treatment have preserved vascular homeostasis and absence of procoagulant cMVs.